PENAKSIR RASIO REGRESI LINEAR SEDERHANA UNTUK RATA-RATA POPULASI MENGGUNAKANKARAKTER TAMBAHAN - Astari Rahmadita; Harison '; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Estimators discussed here are three regression ratio estimators of population mean Y using information on two auxiliary variables Xdan Z under simple random sampling without replacement. They are proposed bySingh, Upadhyaya and Premchandra [4] which is a review of the article “An Improved Version of Regression Ratio Estimator with Two Auxiliary Variables in Sample Surveys.” All estimatorsare biased. The efficient estimator is one with the smallest Mean Square Error (MSE), determined by comparing each type of estimator.